Nanopore long-read RNAseq reveals transcriptional variations in citrus species - Hu, Xiao-Li; You, Congjun; Zhu, Kaikai; Li, Xiaolong; Gong, Jinli; Ma, Haijie; Sun, Xuepeng (Frontiers in Plant Science, 2023)
The number of studies on plant transcriptomes using ONT RNAseq technology is rapidly increasing in recent. It is a powerful method to decipher transcriptomic complexity, particularly alternative splicing (AS) event detection. Citrus plants are the most important widely grown fruit crops. Exploring different AS events in citrus contributes to transcriptome improvement and functional genome study. Here, we performed ONT RNAseq in 9 species (Atalantia buxifolia, Citrus clementina, C. grandis, C. ichangensis, C. reticulata, C. sinensis, Clausena lansium, Fortunella hindsii, and Poncirus trifoliata), accompanied with Illumina sequencing. Non-redundant full-length isoforms were identified between 41,957 and 76,974 per species. Systematic analysis including different types of isoforms, number of isoforms per gene locus, isoform distribution, ORFs and lncRNA prediction and functional annotation were performed mainly focused on novel isoforms, unraveling the capability of novel isoforms detection and characterization. For AS events prediction, A3, RI, and AF were overwhelming types across 9 species. We analyzed isoform similarity and evolutionary relationships in all species. We identified that multiple isoforms derived from orthologous single copy genes among different species were annotated as enzymes, nuclear-related proteins or receptors. Isoforms with extending sequences on 5’, 3’, or both compared with reference genome were filtered out to provide information for transcriptome improvement. Our results provide novel insight into comprehending complex transcriptomes in citrus and valuable information for further investigation on the function of genes with diverse isoforms.